Titanium dioxide/carbon nitride nanosheet nanocomposites for gas phase CO2 photoreduction under UV-visible irradiation - Crake,A; Christoforidis,K; Godin,R; Moss,B; Kafizas,A; Zafeiratos,S; Durrant,J; Petit,C (Applied Catalysis B: Environmental, 2019)
In the field of photocatalysis and particularly that of CO2 photoreduction, the formulation of nanocomposites provids avenues to design a material platform with a unique set of structural, optoelectronic and chemical features thereby addressing shortcomings of single-phase materials and allowing synergistic effects. In this work, inorganic/organic composite photocatalysts for CO2 reduction comprised of titanium dioxide (TiO2) and carbon nitride nanosheets (CNNS) were synthesized using a hydrothermal in-situ growth method. Specifically, pre-formed CNNS were used to synthesize TiO2/CNNS heterostructures with control over the TiO2 facet formation. This synthesis approach improved the catalytic properties by increasing CO2 adsorption capacity and facilitating charge transfer. The materials were characterised by various spectroscopic, imaging, and analytical techniques to investigate their structural (from nano- to macroscale), chemical, and optical properties. TiO2 nanoparticles were efficiently grown on the CNNS. The CO2 adsorption capacity of the composites was measured, and they were tested for CO2 photoreduction under UV-Vis illumination with hydrogen as the reducing agent in a heterogeneous gas-solid system to combine CO2 capture and conversion into a single-step process. Catalytic tests were performed without adding any precious metal co-catalyst. The composites exhibited enhanced CO2 adsorption capacity and photocatalytic CO2 conversion compared to their constituent materials (> ten-fold increase) and outperformed the TiO2 P25 benchmark material. The TiO2/CNNS composite with more {001} TiO2 facets was the most catalytically active. Further investigations using transient absorption spectroscopy (TAS) revealed the control of facet formation improved interfacial transfer at the TiO2/CNNS junction. A photocatalytic mechanism was proposed based on the spectroscopic analyses as well as the CO2 adsorption, and CO2 conversion results.